Analysis of the structure-function relationship of alpha amylase complexed with polyacrylic acid - Porfiri, María Cecilia (2020)
Alpha-amylase is frequently used in technologies that require its immobilization, stabilization or encapsulation. Polyacrylic acid is a very suitable polymer for these purposes because it can bind to enzymes and then be released under certain conditions without altering the functional capacity of enzymes. The consequences produced by polyacrylic acid on alpha-amylase structure and function have been investigated through various techniques. Calorimetric measurements allowed examining the nature of the binding reaction, stoichiometry and affinity, while spectroscopic techniques provided additional information about functional and structural perturbations of the enzyme. Isothermal titration calorimetry (ITC) revealed a mixed interaction and a binding model with a large number of molecules of protein per molecule of polyacrylic acid. One the one hand circular dichroism (CD) spectroscopy showed that alpha-amylase loses its secondary structure in the presence of increasing concentrations of polyacrylic acid, while it is stabilized by the polyelectrolyte at low pH. On the other hand, fluorescence spectra revealed that the three-dimensional enzyme structure was not affected in the microenvironment of tryptophan residues. Differential scanning calorimetry (DSC) thermograms showed that only one domain of alpha-amylase is affected in its conformational stability by the polymer. The unfolding process proved to be partially reversible. Finally, the enzyme retained more than 90 % of its catalytic activity even in excess of the polymer.